2022
DOI: 10.3390/pathogens11101125
|View full text |Cite
|
Sign up to set email alerts
|

Pet Reptiles in Poland as a Potential Source of Transmission of Salmonella

Abstract: Reptiles are considered a potential source of Salmonella transmission to humans. The aim of this research was to determine the incidence of Salmonella in pet reptiles in Poland and to examine Salmonella isolates with regard to their biochemical characteristics, serotype, antimicrobial susceptibility, and pathogenic and zoonotic potential. The research material consisted of 67 reptile faeces samples. The taxonomic affiliation of the Salmonella isolates was determined by MALDI-TOF mass spectrometry, biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…worldwide is a commonly known fact. This carrier status of reptiles is reflected in the health hazards that they present for humans, especially children [1,3,5,29]. Despite this, there are no regulations in place when it comes to the implications of reptile pet shops in the spreading of MDR Salmonella strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…worldwide is a commonly known fact. This carrier status of reptiles is reflected in the health hazards that they present for humans, especially children [1,3,5,29]. Despite this, there are no regulations in place when it comes to the implications of reptile pet shops in the spreading of MDR Salmonella strains.…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention has recently been oriented towards snakes and lizards due to increased interactions between them and humans in domestic environments [1,3,34]. In this sense, it is important to highlight that these reptiles are mainly fed with animal food, representing an important source of Salmonella [15,21,29,35,36]. Previous studies in the United Kingdom reported the important role of commercial feeder rodents in bacterial transmission among reptiles and even their owners [1,37].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other reports, in this study, Salmonella enterica was the most common species isolated from reptiles [10,36,37]. The four subspecies we isolated (S. enterica enterica [I] (3/15), S. enterica salamae [II] (10/15), S. enterica diarizonae [IIIb] (1/15) and S. enterica houtenae [IV] (1/15)) have also been widely reported in different reptile studies, including snakes, turtles, and lizards [6,10,14,29,32]. In addition, Salmonella enterica enterica has been reported in the Gran Canaria Island as the main species isolated from feral cats, although the identified subspecies do not coincide with those found in the California kingsnake [34].…”
Section: Discussionmentioning
confidence: 94%
“…Reptiles have been considered carriers of Salmonella spp. worldwide, and their serological variety and antimicrobial resistance have been studied [10,29,31,32]. Therefore, they may pose a danger as a source of dissemination of the bacterium in the environment, as well as an important cause of animal and human infection, especially in at-risk populations [11,29,33].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella enterica and Salmonella bongori , with their numerous serotypes, are the most important pathogens of this family and frequently associated with infections in ophidians, saurians, and chelonians who may develop disease or serve as asymptomatic carriers [ 40 , 41 , 42 , 43 ].…”
Section: Enterobacteriaceaementioning
confidence: 99%